Illustrating Preferences in Multi-stakeholder System Development Projects through Vignettes. (September 2022) - Weger, Kristin; Leder, Sheri; Eaton, Casey; Bhatia, Garima; Mesmer, Bryan
As organizations respond to the ongoing complex challenges driven by technological, social, and environmental factors, the involvement of multiple stakeholders in the system development process has become the norm. Yet, a gap in literature exists concerning the elicitation of preferences from multiple stakeholders to better understand the requirements of the project. With the use of a vignette and survey research approach, this study demonstrates how perceived individual stakeholder identity within a multi-stakeholder project could influence perceptions towards the importance of system attributes and perceived value for multi-stakeholder projects such as the SPORT satellite. Although the statistical results merely provide a proof of concept for the methods applied, our study has direct implications for the approaches used by practitioners to elicit preferences in complex, multi-stakeholder projects.